Literacy in Judah and Israel: Algorithmic and Forensic Examination of the Arad and Samaria Ostraca - Faigenbaum-Golovin, Shira (Near Eastern archaeology, 2021)
A highly discussed issue in the fields of Hebrew epigraphy and biblical research is the level of literacy in the Iron Age kingdoms of Israel and Judah (Rollston 2010; Davies and Römer 2013; Schmidt 2015). Treating this topic using biblical texts, for example, the references to scribes at the time of a given monarch, may lead to circular argumentation: The reality behind a given account may reflect the time of the authors, who could have lived centuries later and retrojected their own situation back onto earlier history. A preferable methodology is to consider the material evidence—the corpora of Iron Age Hebrew ostraca from archaeological excavations. The idea is to use algorithmic and forensic methods to distinguish between handwritings and thus the number of authors in a given corpus.